Peningkatan Pemahaman Majas Melalui Model Cooperative Learning Tipe Bus Stop dengan Media Diagram Frayer di Kelas VI SD Muhammadiyah 1 Bontang - Salam, Salam (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to improve students' understanding of figurative language material through the application of the Bus Stop cooperative learning model combined with the Frayer Diagram media. The subjects of the study were sixth-grade students of Muhammadiyah 1 Bontang Elementary School. The method used was descriptive qualitative with observation, interview, and documentation techniques. The results of the study showed that the Bus Stop strategy encouraged active interaction between students, allowing them to discuss and provide feedback to each other. Meanwhile, the Frayer Diagram helped students map the concept of figurative language visually and systematically, thus facilitating their understanding of the four types of figurative language taught, namely personification, metaphor, hyperbole, and simile. The combination of these two methods proved effective, with 90% of students showing an increase in their ability to identify and construct figurative sentences. Based on these results, the study recommends the use of cooperative strategies combined with visual media as a more meaningful and enjoyable approach to learning Indonesian, and able to increase student engagement and understanding of figurative language material.